Cathode Interfaces: Effect of Electrolyte Additives on the LiNi0.5Mn0.3Co0.2O2 Surface Film Formation with Lithium and Graphite Negative Electrodes (Adv. Mater. Interfaces 1/2020). Issue 1 (10th January 2020) - Hekmatfar, Maral; Hasa, Ivana; Eghbal, Ramtin; Carvalho, Diogo V.; Moretti, Arianna; Passerini, Stefano
Abstract : The effect of electrolyte additives on the LiNi0.5 Mn0.3 Co0.2 O2 surface film formation in lithium metal and lithium‐ion cells is investigated. A comprehensive XPS study on the cathode/electrolyte interface layer formed on LiNi0.5 Mn0.3 Co0.2 O2 electrodes cycled up to 4.5 V, elucidates the chemical composition, thickness and morphology evolution with different electrolytes allowing a correlation between the interface layer nature and the electrochemical performance. More details can be found in article number 1901500 by Ivana Hasa, Stefano Passerini, and co‐workers.